Nurient Management Trial on Foxtail Millet at Sundarbazar, Lamjung - Ojha, E.; Adhikari, B. B.; Katuwal, Y. (Journal of the Institute of Agriculture and Animal Science, 2018)
Foxtail millet is an indigenous crop known for its rich nutritive value, drought tolerance ability and low input requirements. Though it is grown in marginal condition, it can give the best production with the proper nutrient management for its cultivation. In this respect, an experiment was conducted in Agronomy farm of Lamjung Campus, Sundarbazar during March-June 2017. The main objective of the experiment was to explore the performance of local foxtail millet under different level of nutrients. The experiment was carried out in Randomized Complete Block Design with three replications and seven treatments viz. FYM 6 t/ha, FYM 6 t/ha+60:30:20 kg NPK/ha, 60:30:20 kg NPK/ha, FYM 6t/ha+30:20kg PK/ha, FYM 6t/ha+60:30 kg NK/ha, FYM 6 t/ha+60:30 kg NP/ha and Control (no fertilizers). Results revealed that highest grain yield (2.47t/ha) (152% higher than control), was obtained from FYM 6 t/ha+60:30:20 kg NPK/ha which was followed by 60:30:20 kg NPK/ha (2.45 t/ha) and were statistically at par with each other. The highest grain yield in FYM 6 t/ha+60:30:20 kg NPK/ha was supported by higher no. of grains per panicle (2870), more test weight (1.79 gm) and more harvest index (19.3%). However, the straw yield (12.6t/ha), biological yield (15.02t/ha) along with B: C ratio was found slightly higher in 60:30:20 kg NPK/ha. The growth characters viz. plant height, flag leaf area and panicle length of all the treatments were significantly higher than Control (T7). The treatment having balanced plant nutrients (T2) produced significantly higher yield and can be recommended to mid-hill farmers for obtaining good yield.